From Laboratory Lichens to Colonial Symbiosis. Melchior Treub Bringing German Evolutionary Plant Embryology to the Dutch Empire, 1880-1909 - Wille, Robert-Jan (Studium, 2019)
In this article I demonstrate that Buitenzorg formed an important site for developmental botany or plant embryology. The research stations of Buitenzorg was not only a place for colonial big science, but also a hotspot for new transformations in biology. This article focuses on the evolutionary science practice of Buitenzorg’s director Melchior Treub, and on how he adapted a German style of laboratory biology to the reality of the colonial tropics. In Buitenzorg, plant embryology evolved from a European taxonomic Hilfswissenschaft into a leading sub-discipline of colonial agricultural science. Studying cooperation in nature, Treub was extra keen on experimenting with new forms of political cooperation in the empire.